Molecular diagnostics of neurodegenerative disorders - Agrawal, Megha; Biswas, Abhijit (Frontiers in Molecular Biosciences, 2015)
Molecular diagnostics provide a powerful method to detect and diagnose various neurological diseases such as Alzheimer’s and Parkinson’s disease. The confirmation of such diagnosis allows early detection and subsequent medical counseling that help specific patients to undergo clinically important drug trials. This provides a medical pathway to have better insight of neurogenesis and eventual cure of the neurodegenerative diseases. In this short review, we present recent advances in molecular diagnostics especially biomarkers and imaging spectroscopy for neurological diseases. We describe advances made in Alzheimer’s disease, Parkinson’s disease, Amyotrophic lateral sclerosis and Huntington’s disease, and finally present a perspective on the future directions to provide a framework for further developments and refinements of molecular diagnostics to combat neurodegenerative disorders.